Functional fusion mutant of Candida antarctica lipase B (CalB)expressed in Escherichia coli - Seo, H.S.; Kim, S.E.; Han, K.Y.; Park, J.; Kim, Y.; Sim, S.J.; Lee, J.
Candida antarctica lipase B (CalB)was functionally expressed in the cytoplasm of Escherichia coli Origami (DE3)with the N-terminus fusion of E. coli endogenous proteins. The previously-identified stress responsive proteins through comparative proteome analyses such as malate dehydrogenase (Mdh), spermidine/ putrescine-binding periplasmic protein (PotD), and FKBP-type peptidyl-prolyl cis-trans isomerase (PPIases)(SlyD)dramatically increased the solubility of CalB in E. coli cytoplasm when used as N-terminus fusion partners. We demonstrated that Mdh, PotD, and SlyD were powerful solubility enhancers that presumably facilitated the protein folding of CalB. Moreover, among the various fusion mutants, Mdh-CalB showed the highest hydrolytic activity and was as biologically active as standard CalB. Similarly to the previous report, the electrophoretic properties of CalB indicate that CalB seems to form dimer-based oligomer structures. We evaluated the structural compatibility between the fusion partner protein and CalB, which seems to be of crucial importance upon the bioactive dimer formation of CalB and might affect the substrate accessibility to the enzyme active site, thereby determining the biological activities of the fusion mutants.
Keywords: CALB; FUNCTIONAL EXPRESSION; FUSION MUTANT; BIOACTIVITY; ESCHERICHIA COLI